PELAKSANAAN TUGAS CAMAT DALAM PEMBINAAN ADMINISTRASI PEMERINTAHAN KEPENGHULUAN (STUDI KASUS PADA KEPENGHULUAN DI KECAMATAN PUJUD KABUPATEN ROKAN HILIR) - Febri Harifal; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Implementation of the task in the sub district head coaching administrationkepenghuluan (case studies on kepenghuluan in kecamatan pujud Rokan Hilir). This study aimedto determine the performance of their duties in the construction administration camatkepenghuluan ((case studies on kepenghuluan in kecamatan pujud Rok.an Hilir) and factorinfluence implementation. The Research uses methods of data collection techniques such asinterview, observation and documentation through research informants determined based on thetechnique snowball samplingKeywords: Administration of government, Development, Kepenghuluan